Efektivitas Metode Komunikasi SBAR Dalam Bedside Handover Terhadap Keselamatan Pasien Di Rumah Sakit Melati Tangerang - Febrilya Mustika; Marisa Junianti Manik (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Effective communication during patient handover is essential for patient safety and continuity of nursing care. However, unstructured, traditional handover practices often lead to communication failures and increase the risk of patient safety incidents. Implementing Bedside Handover with the structured SBAR (Situation, Background, Assessment, Recommendation) framework has been shown to improve communication quality among nurses. This study aims to analyze the effectiveness of Bedside Handover training on nurses’ communication. A quasi-experimental pretest-posttest control group design will be conducted among staff nurses in the inpatient wards of Melati Hospital in Tangerang. Participants will be purposively selected based on inclusion criteria and assigned to either the intervention or control group. The intervention group will receive structured training comprising theoretical instruction and SBAR-based role-play simulations, while the control group will continue routine handover practices. Effective communication will be measured using a validated, reliable SBAR-based Bedside Handover observation checklist. Data will be analyzed using univariate and bivariate statistical methods. Within-group comparisons will be performed using the Paired Sample T-Test or Wilcoxon Signed-Rank Test. Between-group differences will be analyzed using the Independent Sample T-Test or Mann–Whitney U Test. This study is expected to provide empirical evidence supporting Bedside Handover training as an effective strategy to improve nurses’ communication, thereby enhancing patient safety and the quality of nursing care.